Free Radicals and Neonatal Brain Injury: From Underlying Pathophysiology to Antioxidant Treatment Perspectives - Silvia Martini; Laura Castellini; Roberta Parladori; Vittoria Paoletti; Arianna Aceti; Luigi Corvaglia (Antioxidants, 2021)
Free radicals play a role of paramount importance in the development of neonatal brain injury. Depending on the pathophysiological mechanisms underlying free radical overproduction and upon specific neonatal characteristics, such as the GA-dependent maturation of antioxidant defenses and of cerebrovascular autoregulation, different profiles of injury have been identified. The growing evidence on the detrimental effects of free radicals on the brain tissue has led to discover not only potential biomarkers for oxidative damage, but also possible neuroprotective therapeutic approaches targeting oxidative stress. While a more extensive validation of free radical biomarkers is required before considering their use in routine neonatal practice, two important treatments endowed with antioxidant properties, such as therapeutic hypothermia and magnesium sulfate, have become part of the standard of care to reduce the risk of neonatal brain injury, and other promising therapeutic strategies are being tested in clinical trials. The implementation of currently available evidence is crucial to optimize neonatal neuroprotection and to develop individualized diagnostic and therapeutic approaches addressing oxidative brain injury, with the final aim of improving the neurological outcome of this population.